The preparation of CaO catalyst from eggshells and its application in biodiesel production from waste cooking oil - Ali, Nur Afiqah; Khairuddin, Nozieana; Tengku Azmi, Tengku Sharifah Marliza; Siddique, Md Bazlul Mobin (Springer, 2022)
This study aims to identify the capability of eggshells to act as catalysts in biodiesel production via the transesterification process. The source of calcium in eggshells is in the form of calcium carbonate. The eggshells undergo a drying process, followed by grinding and calcination at high temperatures to ensure that the calcium carbonate (CaCO3) is fully converted into CaO, which makes it fit for use. The CaO catalyst was prepared from powdered eggshells via calcination at 900 °C for 3 h. The morphological characteristics of CaO were observed by Field Emission Scanning Electron Microscopy and X-ray diffraction. The results obtained show that 1 wt% of catalyst loading has the highest fatty acid methyl ester production compared to others. The outcomes show that the eggshells can be used on a large scale as catalysts to transform waste cooking oil into biodiesel, thereby cutting prices, boosting product yield and fuel characteristics of biodiesel concurrently.